2019
DOI: 10.1080/17538947.2019.1597189
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of earth’s energy budget: synthesis and review

Abstract: The Earth's climate is largely determined by its energy budget. Since the 1960s, satellite remote sensing has been used in estimating these energy budget components at both the top of the atmosphere (TOA) and the surface. Besides the broadband sensors that have been traditionally used for monitoring Earth's Energy Budget (EEB), data from a variety of narrowband sensors aboard both polar-orbiting and geostationary satellites have also been extensively employed to estimate the EEB components. This paper provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(61 citation statements)
references
References 382 publications
(392 reference statements)
0
61
0
Order By: Relevance
“…Earth's weather and climate are driven by the energy received at the surface, which is mainly affected by the contents of the atmosphere, including clouds and aerosols [1,2]. Despite the importance of downward surface radiation fluxes, studies have shown they are not always well estimated from satellite observations nor modeled by climate models [3], and the number of ground sites measuring radiation fluxes is itself a variable number.…”
Section: Introductionmentioning
confidence: 99%
“…Earth's weather and climate are driven by the energy received at the surface, which is mainly affected by the contents of the atmosphere, including clouds and aerosols [1,2]. Despite the importance of downward surface radiation fluxes, studies have shown they are not always well estimated from satellite observations nor modeled by climate models [3], and the number of ground sites measuring radiation fluxes is itself a variable number.…”
Section: Introductionmentioning
confidence: 99%
“…Land surface albedo is one of the most important variables in the study of the surface radiation budget, climate change, and the hydrologic cycle [1]. Remotely sensed albedo products from geostationary satellites provide continuous and consistent measurements over a large region with a very high temporal resolution [2].…”
Section: Introductionmentioning
confidence: 99%
“…They attributed higher albedo and lower incoming solar radiation obtained in wet season to the rain-bearing clouds which pervaded the sky in the rainy season compared to the dry season. It has also been reported that natural phenomena such as wild fire could alter surface albedo [12,[16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…It is a fundamental component of the processes that govern the magnitude, distribution and variability of Earth's climate and climate change [5,6]. Surface albedo is highly variable, depending on many factors, such as landcover types, snow/ice cover, surface roughness or textural characteristics, mineral composition soil moisture content and human activities, such as deforestation, agriculture, irrigation, pollution and urbanization [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%